2021
DOI: 10.4028/www.scientific.net/kem.889.9
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of All-Cellulose Composite from Cotton Fabric via NaOH/Urea Solvent Using Vacuum Bagging-Assisted Process

Abstract: All-cellulose composites (ACCs) become growingly attractive materials in wide range applications due to its green profile, biocompatibility, and enable recycling. In this work, the ACCs was fabricated from cotton fabric (CF) by partial dissolution via aqueous NaOH/urea solution. The alternative ACC fabrication technique using vacuum bagging in the dissolution step was introduced in this study. SEM images confirmed that a vacuum aid during CF-ACC fabrication effectively improved the consolidation of resulting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…14,20−22 Due to their superior mechanical properties, renewability, and environmental benefits, ACCs have shown great potential in a wide range of applications, such as packaging, hydrogels, biomedical devices, photovoltaic devices, electro-active paper, and building materials. 13,22 Cellulose-based materials are considered an intriguing environmentally friendly choice for thermal insulation in buildings with an average thermal conductivity of about 0.040 W/mK. This value aligns with the thermal performance of conventional glass wool and rock wool insulations.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…14,20−22 Due to their superior mechanical properties, renewability, and environmental benefits, ACCs have shown great potential in a wide range of applications, such as packaging, hydrogels, biomedical devices, photovoltaic devices, electro-active paper, and building materials. 13,22 Cellulose-based materials are considered an intriguing environmentally friendly choice for thermal insulation in buildings with an average thermal conductivity of about 0.040 W/mK. This value aligns with the thermal performance of conventional glass wool and rock wool insulations.…”
Section: Introductionmentioning
confidence: 77%
“…Consequently, a mixed solution of NaOH and urea has gained recent attention as a low cost and effective environmentally friendly solvent system for cellulose dissolution for the fabrication of ACCs. Previous studies have demonstrated the successful production of ACCs from a wide range of cellulose textile sources, including cotton, rayon, linen, and flax. The ACCs with a density range of 0.9–1.3 g/cm 3 exhibited high modulus (0.9–28 GPa) and tensile strengths (46–460 MPa), respectively. , Due to their superior mechanical properties, renewability, and environmental benefits, ACCs have shown great potential in a wide range of applications, such as packaging, hydrogels, biomedical devices, photovoltaic devices, electro-active paper, and building materials. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation